Growing electric vehicle adoption: Implications for infrastructure maintenance and the tax burden on families of different funding policies - Kalee E. Burns; Julie L. Hotchkiss (Federal Reserve Bank of Atlanta, 2023)
This paper examines the distribution of the gasoline tax burden in the presence of increased electric vehicle adoption. Automobile manufacturers and even some states have ambitious goals to phase out gas-powered cars. However, in spite of these plans, the primary source of automobile infrastructure funding in the United States continues to be gasoline taxes. Less demand for gasoline threatens this source of revenue for maintaining roads and further shifts the burden of the tax toward consumers who can't afford the still relatively expensive electric vehicles. The analysis here illustrates the fundamental regressivity of the gasoline tax, then simulates the distributional impact of replacing the current gas tax with a lump-sum/income tax with different assessment rules designed to replace revenue generated by the gasoline tax. For example, many states are considering switching from a gas tax to a tax based on miles driven to shore up infrastructure funding. Alternatively, the required revenue could be paid equally across income quartiles or assessed based on income. Not surprisingly, the degree of regressivity of replacing the gasoline tax depends on how the tax is assessed across the income distribution.
Keywords: H22; Q21; D11; 330; gas tax; incidence; consumer demand system; income distribution; equity